Academic publishing in Mexico - Deal, Carl (SALALM Secretariat AlbuquerqueUS)
Based upon interviews with major book vendors specializing in serving academic libraries in the United States, with the most important Mexican academic publishers and with academic librarians. Seeks to isolate the dynamics of Mexican academic publishing and organization of the book trade.